Penilaian Kemampuan Literasi Dini melalui Metode Bercerita (Storytelling) - Dwi Nomi Pura; E. Jusmadi; R. Aulia Chadhavi; A. Fatma Gusmiarti; A. Nur Rahma (Early Childhood Research and Practice, 2026)
Early literacy is an important foundation in the language and cognitive development of early childhood. The development of early literacy skills needs to be carried out through meaningful and engaging learning activities that are appropriate to children's developmental characteristics. One of the learning methods that can support the development of early literacy is storytelling. This study aims to analyze the assessment of early literacy skills through storytelling activities in early childhood learning. The research used a qualitative approach with a descriptive method. The subjects of this study were children aged 5–6 years at an early childhood education institution in Bengkulu City. The selection of research subjects was conducted using purposive sampling based on children's involvement in storytelling activities. Data were collected through observation, documentation, and performance assessment during storytelling activities. The indicators used to assess early literacy skills included the ability to listen to stories, understand story content, recognize new vocabulary, answer questions related to the story, and retell stories using their own language. The data were analyzed using qualitative descriptive analysis through data reduction, data presentation, and conclusion drawing. The results of the study indicate that storytelling activities contribute positively to the development of early literacy skills in children. Most children showed good ability in listening to stories, understanding story content, and responding to questions given by the teacher. In addition, several children were able to retell the story in simple language and even develop the story with their own imagination. Therefore, storytelling can be used not only as a learning method but also as an authentic assessment tool to evaluate early literacy development in early childhood education.